Allied in danger : a capital crimes novel - Truman, Margaret, 1924-2008; Bain, Donald, 1935-2017 (Capital crimes, 2018)
David Portland's life is upended when his son Trevor dies mysteriously in Nigeria, while employed by a suspicious security/mercenary company. Information he learns will send Portland down a rabbit-hole of deadly deception - one which he hopes will lead him to the truth about his son's death. Meanwhile, Robert Brixton has been hired to look into a fraudulent charity and a criminal warlord in Nigeria. Their interconnected cases will take Brixton to Nigeria, into that country's Heart of Darkness and on one of the most violent and dangerous journeys of his life.